Sprinting to second place: A meta-analysis comparing SIT vs HIIT to augment time trial performance - Rosenblat, M. A.; Thomas, S. G. (Applied Physiology, Nutrition, and Metabolism, 2018)
Interval training elicits profound improvements in cardiovascular fitness in both trained and untrained individuals. The objective of this review was to systematically compare the effects of high-intensity interval training (HIIT) versus sprint interval training (SIT) on time trial performance. The electronic search included all publication years up to and including December 28, 2017, published in English, included both HIIT and SIT intervention groups, and incorporated time-trial (TT) performance. Medline (Ovid) and SPORTDiscus (EBSCOhost) yielded a combined 8235 results. Following the removal of 1922 duplicates, 6313 titles and abstracts were screened. Eight studies met the inclusion criteria for the qualitative analysis and 7 studies were used in a meta-analysis. Study quality on the PEDro scale averaged 4.9 ± 0.6 out of 10. All studies included participants who were actively participating in endurance sport for at least 2.5 years (2.5 to 7.0 years). Seven of the eight included trials favoured HIIT over SIT, only three of which reached significance. Seven studies (135 participants) were included in the quantitative analysis and indicate improvement in TT performance in the HIIT group with an ES of -0.50, 90% CL (-0.79, -0.20), p= 0.006, when compared to the SIT group, equivalent to a 1.6% faster completion. An interval training program consisting of HIIT leads to a greater improvement in endurance sport performance compared to SIT in trained and highly-trained male endurance athletes.